Pretreatment Clinical Variables Associated With the Response to Intravitreal Bevacisumab (Avastin) Injection In Patients With Persistent Diabetic Macular Edema - Fareed A. Warid AL-Laftah; Maha Elshafie; Dr.Mustafa Alhashimi; Aant Pai (مجلة كلية الطب, 2010)
Background: The purpose of the study is to determine whether the pre-treatment clinical systemic variables and optical coherence tomographic (OCT) findings are associated with the subsequent response to the intravitreal Bevacisumab (IVB) in eyes with diabetic macular edema (DME). Patients and Methods: 38 patients (45 eyes) with refractory diabetic macular edema. ; 16 females, 22 males and mean age was 57.5 year. All patients had DME not responded to other treatments. Complete eye examination; BCVA* (represented as LOGMAR for adequate statistical analysis), slitlamp exam, intraocular pressure measurement, stereoscopic biomicroscopy of the macula, and morphologic patterns of diabetic macular edema demonstrated by OCT. All patients had intravitreal injection of 0.05mL =1.25 mg Bevacizumab (Avastin; Genentech, Inc.,San Francisco, CA), and followed up for 3 months. The pre and post-operative follow-up data were analyzed by Student-t test and Mann-Whitney test for two main outcome measures; visual acuity (LOGMAR) & central foveal thickness (CFT) changes over a period of three months, and data include demographic factors, type, duration and control of diabetes mellitus (HbA1C%), grade of diabetic retinopathy, renal function (serum creatinine level), serum cholesterol, blood pressure control and previous treatment by focal laser and/or intravitreal triamcinolone injection. Results: The visual acuity and CRT improved in 30/45 eyes (67%) and 32/45 eyes (72%) respectively during a mean follow-up time of three months. The mean LogMAR visual acuities were 0.64 (SD ± 0.34), 0.61 (SD ± 0.31) and 0.60 (SD ± 0.32) at pre-injection, at 1 month post-injection and at 3 months post-injection respectively; but this mean increase in vision was statistically not significant (P value = 0.099). The mean foveal thicknesses were 444.95 μ (SD ± 127.36), 394.95 μ (SD ± 138.03) and 378.32 μ (SD ± 112.01) at pre-injection, 1 month post-injection and 3 months post-injection respectively, this decrease in the foveal thickness was statistically significant (P value < 0.001). The LogMAR and CFT values before and after IVB injection showed significant statistical correlations =(p< 0.05) in relationship to variables of diabetic duration, diabetic control (HbA1c), and OCT pattern of macular edema, serum creatinine and cholesterol. Conclusions: chronicity and inadequate control of diabetes mellitus, nephropathy, hyperlipidemia and =presence of vitreomacular attachment (VMA) are factors associated with poor vision progress after intravitreal Bevacisumab injection.